Pengembangan Sumber Belajar Berbasis Google Sites untuk Meningkatkan Keterampilan Proses dan Penguasaan Konsep Rangkaian Listrik pada Siswa Kelas VI SD - Hidayat Hidayat; Otib Satibi Hidayat; Widiasih Widiasih (Jurnal Penelitian Pendidikan IPA, 2023)
Trends in International Mathematics and Science Study (TIMSS) Indonesia's results in the last four editions ranked 44 out of 49 countries can show students' low literacy and science process skills. The research aims to develop products by utilizing google sites-based websites to improve students understanding of concepts and science process skills.Â  ADDIE research method with steps of analyzing needs, designing products, developing products, trials and applying development results to students. The instruments used are expert validation instruments and data analysis techniques with triangulation, namely observations, interviews, and tests to see the effectiveness of the product. The validation results of the Material Expert showed a score of 4.3 indicating a very valid category, the Linguist showed a score of 4.46 indicating the category was very valid, the Media Expert showed a score of 4.69 indicating the category was very valid, and the Pedagogy Expert showed a score of 4.54 indicating the category was very valid. The effectiveness rate of this product is quite high, namely 19 students or 82.6% achieved and measured by N-Gain the score is at 0.5 with a moderate category. Aspects of electrical observing skills 82.14% or very high categories, grouping 92.86% very high categories, interpreting an average of 82.14% very high, forecasting average incidence 85.71% very high, formulating hypotheses averaging 89.29 very high, formulating product designs averaging 96.43% very high categories and communicating aspects 78.57% high categories. These results can be concluded that the development of learning resources by utilizing google sites as a learning resource can increase understanding of concepts and encourage students to be actively involved in learning.